3D Modeling Parallel Coupled-Line Bandpass Filter Based on Coplanar Waveguide MMIC Multilayer Technology - Rizqi Eka Putri; Emerson Pascawira Sinulingga; Suherman Suherman (Jurusan Teknik Elektro UIN Sunan Gunung Djati Bandung, 2019)
Electromagnetic modeling technique on monolithic microwave integrated circuit (MMIC) coplanar waveguide (CPW) multilayer have been developed to accurately model the Parallel Coupled-Line Bandpass Filter. The 3D modeling technique shows the simulation results that are optimum. Several simulation steps have been demonstrated and compared on the design of Parallel Coupled-Line Bandpass Filters. Based on the 3D modeling, S11-Return Loss and S21-Insertion Loss of -22.6 dB and and 2.94 dB are obtained respectively. In addition, it is shown the best frequency response from the design of the Parallel Coupled-Line Bandpass Filter.